Corporate Governance and Organizational Growth: A Case of Nepalese Commercial Banks - Thagunna, Prakash; Thakuri, Pratibha; Thapa, Rabina; Chaudhary, Raman Kr.; Dahal, Roshan; Das, Roshan K. (Nepalese Journal of Finance, 2024)
This study examines the impact of corporate governance on the organizational growth in the context of Nepalese commercial banks. The selected dependent variables are return on equity and return on assets. Similarly, the selected independent variables are board meeting, board diversity, audit committee size, board interdependence, firm age and board size. The study is based on secondary data of 15 commercial banks with 105 observations for the period from 2015/16 to 2021/22. The data were collected from Banking and Financial Statistics published by Nepal Rastra Bank, publications and websites of Nepal Rastra Bank (NRB) and annual reports of the selected commercial banks. The correlation coefficients and regression models are estimated to test the significance and importance of corporate governance on the organizational growth in the context of Nepalese commercial banks.The study showed that board independence has a positive impact on return on equity. It means that higher the number of independent directors on the board, higher would be the return on equity. Similarly, board diversity has a positive effect on return on assets and return on equity. It means that increase in proportion female directors on board leads to increase in return on assets and return on equity. The results of the study also showed that audit committee has a positive impact on return on assets and return on equity. It implies that larger the size of audit committee, higher would be the return on assets and return on equity. However, firm age has a positive impact on return on assets. This shows that increase in firm age leads to increase in return on assets. Similarly, board size has a positive impact on return on assets and return on equity. It implies that larger the board size, higher would be the return on assets and return on equity.